Mating compatibility among Bactrocera cucurbitae (Diptera: Tephritidae) populations from three different origins. (7th September 2010) - Sookar, P.; Haq, I.; Jessup, A.; McInnis, D.; Franz, G.; Wornoayporn, V.; Permalloo, S.
Abstract: Distinct host ranges of the melon fly, Bactrocera cucurbitae (Coquillett), have been reported among different island populations, suggesting significant genetic divergence. Thus, for the application of the sterile insect technique (SIT), it is important to ensure that released flies are sexually fully compatible with each other and with the laboratory strains. Mating tests among the following strains of the melon fly, B. cucurbitae : Mauritius laboratory‐adapted (35 generations), Seychelles laboratory‐adapted (24 generations), and Hawaii genetic sexing strain (90 generations), were conducted in field cages at the FAO/IAEA Agriculture and Biotechnology Laboratories in Seibersdorf, Austria during the months of August/September 2009. The genetic sexing strain, developed in Hawaii in 2001, allows separation of females and males on the basis of pupal colour. Two separate series of trials were run simultaneously. In the first, melon fly females from Mauritius were the target strain and the competing males were from Mauritius, Seychelles, and Hawaii (GSS). In the second trial, melon fly females from the Seychelles selected among competing males from the same three populations. Sexual activity was similar among the melon fly populations and no significant non‐random, assortative mating was observed. Therefore, it is suggested that melon flies from Mauritius, Seychelles and the Hawaii are compatible, at least under semi‐natural conditions.